Effects of fresh and composted Azolla on soil chemical properties - Abdul Rashid, Nur Syahirah; Jalloh, Mohamadu Boyie; Azman, Elisa Azura; Awang, Azwan; Ahmed, Osumanu Haruna; Tajidin, Nor Elliza (Universiti Putra Malaysia Press, 2024)
The rise in chemical fertilizer use in Malaysia raises concerns about soil degradation and potential long-term yield reductions, highlighting the importance of using organic matter for soil restoration. Azolla has been extensively studied as an alternative soil amendment due to its high nitrogen and nutrient content, as well as its rapid growth. However, the effects of fresh and composted Azolla amendments on soil chemical properties are not yet fully understood. A soil incubation study was thus conducted to determine the effects of fresh and composted Azolla on soil chemical properties over a 3-month incubation period. The soil treatments consisted of non-amended soil (control); fresh Azolla at 3, 6, and 9% w/w; and composted Azolla at 1, 2, and 3% w/w, with soil water holding capacity maintained at 55% throughout the incubation period. The collected soil samples were analyzed for soil pH and electrical conductivity (EC), total carbon (C) and nitrogen (N), available phosphorus, exchangeable bases—potassium (K), calcium, and magnesium, using inductively coupled plasma optical emission spectrometry, and cation exchange capacity (CEC). All data were subjected to variance analysis for statistical analysis. The study revealed significant effects of interaction between soil treatments and incubation periods for all soil parameters. At the end of the incubation period, the soil treated with 3% composted Azolla exhibited higher soil EC, total C and N, exchangeable K, and CEC compared to other soil treatments. The 3% fresh Azolla treatments were also observed to improve the soil’s exchangeable calcium by the end of the incubation period. In conclusion, 3% composted Azolla is best to help restore soil nutrient levels for crop uptake.